Acquisition and analysis of EMG data during special slalom for comparative equipment evaluation - Marcolin, G.; Petrone, N. (The Engineering of sport 7, Volume 2, 2008)
The aim of this work was to develop a method for acquisition and analysis of EMG data during special slalom in the snow field. In particular the purpose was to find a reliable method for the acquisition of EMG signals on the slopes that could be synchronously correlated to the pole passing instants, the skier body posture and the ski angle of attack. This method allowed to evaluate the biomechanics of skiing technique and to study the effect of racing slalom skis equipment with different tuning conditions. A PDA PocketEMG (BTS-Italy) was employed for data acquisition: its dimensions and weight were optimal for not influencing skiers' behaviour. This compact System allowed to collect eight EMG channels from the right leg and back of the skier, two Biometrics goniometers fixed at the right knee and at the right hip and 2 accelerometers placed on the tibial shin protections to have the timing with respect to the pole passing. All data were recorded at 1kHz. Two inertial plat-forms X-Sens Mti were applied to the skis and synchronously recorded at 1000 Hz. A professional skier performed several slalom courses with different tuning conditions between 10 poles; in addition after passing the 10th pole, a 60 m free slalom course was performed. For a given ski tuning, the tester technique was compared in terms of timing pattern at the poles, intensity of EMG activation at the different muscles and ski angle of attack in order to underline possible differences due to skiing equipment.